The Baculovirus Expression System Expresses Chimeric RHDV VLPs as Bivalent Vaccine Candidates for Classic RHDV (GI.1) and RHDV2 (GI.2) - Yan Wang; Yiyang Fan; Ruixiang Bi; Yapeng Zhao; Wanning Gao; Derong Zhang; Jialin Bai (Vaccines, 2025)
Background: Rabbit hemorrhagic disease (RHD) is an acute, hemorrhagic and highly lethal infectious disease caused by rabbit hemorrhagic disease virus (RHDV), which causes huge economic losses to the rabbit breeding industry. Moreover, there is limited cross-protection between the two different serotypes of classic RHDV (GI.1) and RHDV2 (GI.2). The shortcomings of traditional inactivated vaccines have led to the development of novel subunit vaccines that can protect against both strains, and the VP60 capsid protein is the ideal antigenic protein. This study focused on developing a bivalent RHDV vaccine that can prevent infection with both GI.1 and GI.2 strains. Methodology: Baculovirus vectors containing classic RHDV and RHDV2 VP60 were co-transfected with linearized baculovirus into sf9 cells and transferred to baculovirus via homologous recombination of the VP60 gene. Infected sf9 cells were lysed, and after purification via Ni-NTA chromatography, VLPs were observed using transmission electron microscopy (TEM). In order to evaluate the immunogenicity of the chimeric RHDV VLP vaccine in rabbits, the RHDV VP60-specific antibody, IL-4, IFN-γ and neutralizing antibody titers were analyzed in serum using ELISA and HI. Results: The recombinant baculovirus system successfully expressed chimeric RHDV VLPs with a diameter of 32–40 nm. After immunization, it could produce specific antibodies, IL-4 and IFN-γ. Following the second immunization, neutralizing antibodies, determined using hemagglutination inhibition (HI) assays, were elicited. Conclusions: These data show that the chimeric RHDV VLP bivalent vaccine for immunized New Zealand rabbits can induce humoral immunity and cellular immunity in vivo, and the immunization effect of the high-dose group is similar to that of the current commercial vaccine.